Impact of Tourism Consumption on GDP. The Role of Imports - Raúl Hernández Martín (Fondazione Eni Enrico Mattei (FEEM), 2004)
The aim of this paper is to analyse the effects of tourism consumption on imports. The basic idea is that conversion of tourism expenditure into value added and GP depends on the effect of the former on imports. Imports are leakages that reduce the economic impact of tourism in a destination and this seams to be especially important in the case of small islands. After finding some stylised facts about the evolution of tourism consumption and imports in the Canary Islands, the paper presents two different methodologies, Keynesian multipliers and input-output analysis. The Canary Islands are used as a case study for estimating the impact of consumption made by tourists on imports.
Keywords: L83; F10; R15; 330; Economic impact; Imports; Keynesian multiplier; Input-output model; Canary Islands; Tourismus; Privater Konsum; Import; Multiplikator; Input-Output-Analyse; Schätzung; Kanarische Inseln